Synergetic Education as Basis of Forming New Outlook in Learners - A M Hamidullin; A G Madzhuga (RUDN Journal of Psychology and Pedagogics, 2012)
The essence of the concept «synergetic education» is considered and the basic principles of synergetic education are characterized, the role of synergetic thinking in forming the scientific world view is shown in the article. The authors developed and scientifically proved the theoretical and conceptual model of forming the synergetic culture of the personality in the context of the priorities of a modern education system.